(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2021)
BACKGROUNG: An overall annual incidence of acute upper gastrointestinal haemorrhage has been estimated to be 40-150 per 1,00,000 populations (1,2), leads to annual hospital admission rate of approximately 100 per 1,00,000 hospital admissions, and has significant associated morbidity and mortality, especially in the elderly. Gastrointestinal bleeding, which is most commonly arises from mucosal erosive disease accounts for up to 20,000 deaths annually. Various risk scoring systems have been recently developed to predict clinical Outcomes and need of ICU admission in patients with upper gastrointestinal bleeding (UGIB) or hematemesis. The two commonly used scoring systems include full Rockall score (RS) and the Glasgow Blatchford score (GBS). MATERIAL AND METHOD: An observational, study was conducted on 50 patients with obvious symptoms of UGIB in the emergency department of SVPIMSR, Ahmedabad. full Rockall score (RS) and the Glasgow-Blatchford score (GBS)were calculated. Data was collected from hospital iHiS system and analysed in epi info (version 7.3.2.1) CDC software. P <0.05 was considered statistically significant. RESULTS: A total of 50 patients with UGIB were included in the study of which 72% were male and 28% were female. The mean age of patients was 47.36±16.69 years. It was found that majority of patients (44%) were in the age group of 40-60 years. Mean frequency of hematemesis was significantly higher in non-survival patient in comparison with survival ones (3.1±1.1 versus 1.85±0.62, p=0.0004). In mortality prediction full Rockall score is better than GBS (p value 0.0769 versus 0.9612). Full RS system seems to be better than GBS in predicting mortality and need for ICU admission in patients presented with hematemesis.